FACEBOOK : A Product Of Popular Culture And The Virtual Interreligious Dynamics - NELSON SEMOL KALAY (KENOSIS: Jurnal Kajian Teologi, 2018)
Popular Culture especially Facebook has become a part our everyday life. Religious communities such as church is also using this media of communication to support its ministerial purposes. In this article, I try to explore about the ideas of Facebook in order to see to what extend this media has already contributed not merely for any particular religion, but also for strengthening interreligious relations. This article begins with a consideration on why we should pay attention on Facebook in our theological discourses, followed by a brief description why it has been said as a form of popular culture. In the next section, I will analyze social, existential or hermeneutical, and transcendent dimensions functions of Facebook setting out from Gordon Lynch’s theory. In the end, I will specifically highlight how Facebook can contribute for interreligious dynamics. This part ends up with three considerations that Facebook has built an online interreligious community, increased public awareness on social and political issues, and bridged the gap in the spatially-segregated community.